Optimizing a Local Resource-Based Business Model for the Gadod Weaving Industry: Increasing Brand Awareness and Customer Engagement - Umam, Muhammad Khoirul; Askarno, Askarno; Rochmansyah, Bagaskara Nur (Journal Research of Social Science, Economics, and Management, 2025)
The Gadod Weaving Industry in Majalengka, a cultural heritage of high value, faces challenges due to low brand awareness and customer engagement caused by a traditional business model that has not undergone digital transformation. This research aims to optimize a business model based on local resources through collaboration between culture and digital technology to increase brand awareness and customer engagement. This study uses a descriptive qualitative approach with a case study on Gadod Weaving artisans in Nunuk Baru Village. The research findings present a business model design for Tenun Gadod based on local resources, emphasizing community collaboration, cultural storytelling, and digital marketing. The digital campaign "Gadod Weaving for the World" showed significant improvements: content reach exceeded 32,000 impressions with 65.2% new audience, an interaction rate of 1.83% (exceeding the national average), a +211% increase in website active users, and a +306% increase in online interaction activity. The main outcomes of this research include the BMC-VPC business model, branding strategy, training for local content creators, and digital collaboration with regional media. The implementation of the R.A.I.S.E method has proven effective in integrating research, business strategy, and culture-based digital promotion. The research results demonstrate that cultural storytelling and cross-sector collaboration can increase the economic value and image of Tenun Gadod as a highly competitive local product. This strategy has the potential to be replicated in other traditional weaving industries, supporting cultural preservation while strengthening the creative economy in the region.